Vagus nerve stimulation initiated late during ischemia, but not reperfusion, exerts cardioprotection via amelioration of cardiac mitochondrial dysfunction - Shinlapawittayatorn,K. (Elsevier, 2015)
© 2014 Heart Rhythm Society. All rights reserved. Objective This study aimed to determine whether VNS applied during ischemia or at the onset of reperfusion exerts differential cardioprotection against cardiac I/R injury. Methods Twenty-eight swine (25-30 kg) were randomized into 4 groups: Control (sham-operated, no VNS), VNS-ischemia (VNS applied during ischemia), VNS-reperfusion (VNS applied during reperfusion), and VNS-ischemia+atropine (VNS applied during ischemia with 1 mg/kg atropine administration). Ischemia was induced by left anterior descending (LAD) coronary artery occlusion for 60 minutes, followed by 120 minutes of reperfusion. VNS was applied either 30 minutes after LAD coronary artery occlusion or at the onset of reperfusion and continued until the end of reperfusion. Cardiac function, infarct size, myocardial levels of connexin 43, cytochrome c, tumor necrosis factor α, and interleukin 4, and cardiac mitochondrial function were determined. Results VNS applied 30 minutes after LAD coronary artery occlusion, but not at reperfusion, markedly reduced ventricular fibrillation incidence and infarct size (~59%), improved cardiac function; attenuated cardiac mitochondrial reactive oxygen species production, depolarization, swelling, and cytochrome c release; and increased the amount of phosphorylated connexin 43 and interleukin 4 as compared with the Control group. These beneficial effects of VNS were abolished by atropine. Conclusion VNS could provide significant cardioprotective effects even when initiated later during ischemia, but was not effective after reperfusion. These findings indicate the importance of timing of VNS initiation and warrant the potential clinical application of VNS in protecting myocardium at risk of I/R injury. Background We previously reported that vagus nerve stimulation (VNS) applied immediately at the onset of cardiac ischemia provides cardioprotection against cardiac ischemic-reperfusion (I/R) injury.